Pengembangan Potensi Berwirausaha di Kalangan Mahasiswa UINSU (Berjualan Keripik Pisang Cokelat Lumer) - Zulqaidah Zulqaidah; Hasriyati Harahap; Ella Nurmaini (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
An entrepreneur is an innovator who can turn an opportunity into a business idea that can add value. Entrepreneurs also play a big role in the economy, namely by contributing to increasing economic growth and creating jobs which will have an impact on increasing state income. This research aims to determine the entrepreneurial potential among students at the North Sumatra State Islamic University by running a melted chocolate banana chips business. This research method is included in the qualitative research type, by conducting various literature reviews on entrepreneurship. The population studied in this research includes all individuals on the UIN North Sumatra campus, from children to adults. The results of the research show that this activity has a positive impact on a student to dare to try, never give up, train self-confidence and train the entrepreneurial spirit that exists in students. Based on the results of these activities, it can be concluded that the importance of developing entrepreneurship among students is very significant. Through this development, the younger generation can grow and develop better. Currently, the level of student entrepreneurial potential is at a very high and high level.